Cytokine Profile and Intracellular Matrix Component Degradation Indicators in Male Ejaculate with Chronic Urethritis Before and Following the Treatment - Sergeevna, Chepurnova Natalia (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The present study was aimed to identify the local level alterations in pro-inflammatory, anti-inflammatory cytokines, and matrix metalloproteinase indicators as well as their tissue inhibitors in male ejaculate with chronic urethritis. Materials and Methods: Antiviral therapy was given as preparation of valacyclovir, administered per os in dosage 500 mg twice a day during 10 days, then 500 mg once a day during 20 days; antibacterial therapy was implemented with doxycycline in dosage 100 mg twice a day during 10 days. Immunomodulator was used as recombinant human interleukin-2 in dosage 500 thousand IU 1.0 ml subcutaneously in the shoulder area every day. Laboratory researches included cytokine status and acute-phase protein analyses initially and after 28 days it has been evaluated with specific reagents of â€œR&D Diagnostics Inc.â€ (USA) by means of sandwich-variant solid-phase immunoassay analysis. The results were processed with immunoassay analyzer â€œMultiscanâ€ (Finland). Cytokine number and metalloproteinase system indicators were evaluated with the help of calibration curve by means of the computer program. The number was evaluated in PN/mlÐ¸Ð»Ð¸NG/ml. The data were statistically processed with Statistica 10 and R. Conclusion: The study presents the local level cytokine response phenotypes in men with chronic herpetic, chlamydial, and mixed urethritides depending on the etiologic factor based on immunologic indicators, defined by means of specific and highly sensitive statistic methods. Additional differential markers of chronic urethritides in men have been proposed. Immunologic evaluation of the efficiency of the etiotropic therapy as well as schemes coupled with cytokine therapy, defining effects of the latter per se, has been carried.